2017
DOI: 10.1061/jpeodx.0000007
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Pavement’s Flood Resilience

Abstract: Although several studies observed pavement responses after flooding, no detailed quantification has been done to date. This paper has estimated different pavements' performances with flooding to identify flood-resilient roads. This was shown through (1) new roughness and rutting-based road deterioration (RD) models, (2) the relationship between changes in roughness [International Roughness Index (IRI)] versus time and modulus of resilience (Mr) loss at granular and subgrade layers versus time, and (3) flood co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Future work can incorporate observations on how road networks are impacted by relative contributions of specific drivers from marine sources (Serafin et al., 2017) and others, such as pluvial (Dave et al., 2021; Evans et al., 2020; Kelleher & McPhillips, 2020; Neumann et al., 2021; Pregnolato et al., 2017) or groundwater flooding (Habel et al., 2020, 2017; Plane et al., 2019; Rotzoll & Fletcher, 2013), or the potential importance of variability in flood duration (Arrighi et al., 2021; Darestani et al., 2021; de Bruijn et al., 2019; Najibi & Devineni, 2018; Pezza & White, 2021; Sweet et al., 2014). Adding traffic dynamics either through graph‐based approaches (e.g., Dong et al., 2022), or agent‐based traffic simulations (e.g., Hummel et al., 2020; Papakonstantinou et al., 2019) would also enrich future work, as would further investigation of material and mechanical properties of roadways to understand the event conditions likely to cause permanent damage (e.g., Khan et al., 2014, 2017; Mallick et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Future work can incorporate observations on how road networks are impacted by relative contributions of specific drivers from marine sources (Serafin et al., 2017) and others, such as pluvial (Dave et al., 2021; Evans et al., 2020; Kelleher & McPhillips, 2020; Neumann et al., 2021; Pregnolato et al., 2017) or groundwater flooding (Habel et al., 2020, 2017; Plane et al., 2019; Rotzoll & Fletcher, 2013), or the potential importance of variability in flood duration (Arrighi et al., 2021; Darestani et al., 2021; de Bruijn et al., 2019; Najibi & Devineni, 2018; Pezza & White, 2021; Sweet et al., 2014). Adding traffic dynamics either through graph‐based approaches (e.g., Dong et al., 2022), or agent‐based traffic simulations (e.g., Hummel et al., 2020; Papakonstantinou et al., 2019) would also enrich future work, as would further investigation of material and mechanical properties of roadways to understand the event conditions likely to cause permanent damage (e.g., Khan et al., 2014, 2017; Mallick et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IRI gives a holistic assessment of functional performance under inundation. Previous studies evaluating concrete and flexible pavement flood impact employed IRI performance in both modeling and field analysis ( 8 , 10 , 12 , 17 , 46 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported changes in infrastructure deterioration trajectories because of changes in prolonged climate loads, extreme climate loads or both ( 5 , 8 , 15 , 16 ). Some studies have further investigated changes in performance and service life by quantifying damage, damage risk, pavement fragility, and asset value at risk per probability of flood occurrence, to promote climate change adaptation for pavement resilience in various climate scenarios ( 9 , 11 , 17 ). These studies provided insight into various factors of pavement resilience and sustainability performance under various climate change scenarios.…”
mentioning
confidence: 99%
“…Therefore, this study quantified the reduction in PSL (indicator of the long-term pavement performance) resulting from inundation for asphalt pavements. Several studies evaluated flood-induced damage by comparing inundated and non-inundated sections utilizing only post-inundation pavement testing data, since pre-inundation pavement testing data were unavailable (9,10,12,14). It is well recognized that different pavement sections may have different pavement structure, pavement condition, foundation type, traffic level, and so forth.…”
Section: Knowledge Gaps In the Literaturementioning
confidence: 99%
“…Considerable research has been conducted in recent years to evaluate the impacts of inundation on pavement functional and structural conditions ( 9 14 ). Yet, limited studies quantified how the change in pavement conditions affect the long-term pavement performance (in relation to reduction in the pavement service life [PSL]) and pavement life-cycle costs.…”
mentioning
confidence: 99%